Upaya Retensi Karyawan Mekanik Dan Operator Potensial Melalui Program Pelatihan Dan Pengembangan Karir Pada Pt Gagah Putera Satria - Putri Kurnia Pratiwi; Rahmatul Jannatin Naimah (BIMA: Jurnal Bisnis dan Manajemen, 2023)
Company achievement is closely related to the quality of its employees. Therefore, Human Resource Management (HRM) must build, motivate and manage the maximum human resources that companies have to increase the ability of employees investments. This has resulted in the company PT Gagah Putera Satria having to make efforts to retain employees or maintain and provide training and career development for employees in order to reduce the company's turnover rate. The purpose of this study, to find the causes,retention efforts, training, career development as well as advice given to the company.The method used to describe the data in this study is qualitative or descriptive, analysis of research data is carried out such as observation and interviews. The results of this study, it is very difficult to find employees because as a result there are many mining companies offering competitionvalue which is quite good and also not sufficient enough in terms of employee facilities, one of which is the internet network for communication access, as well as it is very important to increase company benefits to ensure company welfare.